Using Metacognitive Strategies to Improve Reading Comprehension and Solve a Word Problem - Tomo Djudin (Institute for Research and Scientific Publications STKIP Singkawang, 2017)
This article describes briefly the theories of metacognition and the impacts of metacognitive skills on learning. The differences between cognitive strategy and metacognitive strategy were mentioned. Some strategies to improve students' meta cognition skills in the classroom explored as well. Based on the theories, two models of metacognitive strategies instruction for deeply understanding in reading textbook and for finding a solution of words physics problem solving were developed. These models will enable students to be independent and strategic learners.